Willingness to Buy Pro-Israel Fast Food Post-Boycott: A Jakarta Consumer Study - Arista Ivana Putri; Nadya Fadillah Fidhyallah; Rizka Zakiah (Jurnal Bisnis, Manajemen, dan Keuangan, 2024)
This study aims to examine the effect of animosity and consumer ethnocentrism on willingness to buy through product judgement among consumers of pro-Israel fast food products in DKI Jakarta following the boycott movement. A quantitative method was applied using a survey of 231 respondents who had consumed KFC within the past six months. Data were analyzed using Structural Equation Modeling (SEM) with SPSS and AMOS. Results revealed that animosity significantly affects product judgement but not directly willingness to buy. Consumer ethnocentrism showed no significant effect on either product judgement or willingness to buy. Product judgement significantly influences willingness to buy and mediates the relationship between animosity and willingness to buy. The study contributes to understanding social-value-based marketing.